A Meta-Analysis of Schema Instruction on the Problem-Solving Performance of Elementary School Students. (October 2017) - Peltier, Corey; Vannest, Kimberly J.
A variety of instructional practices have been recommended to increase the problem-solving (PS) performance of elementary school children. The purpose of this meta-analysis was to systematically review research on the use of schema instruction to increase the PS performance of elementary school–age students. A total of 21 studies, with 3, 408 elementary school student participants, and 324 students identified with disabilities, met criteria. Moderator analysis includes assignment, implementer, instruction, problem type, and treatment duration. Results indicate an overall effect size (Hedge's g) for schema instruction of 1.57 (.043), CI95 [1.52, 1.61] for immediate PS and 1.09 (.046), CI95 [1.04, 1.14] for transfer PS. Moderator analysis, future research, and implications for practice are discussed.